ChemInform Abstract: The Crystal Structures of m, o‐Ce3Pt4Sn6 and Ce1‐xPt6Al13+2x. Issue 29 (June 2016) - Paschinger, Werner; Yubuta, Kunio; Saiga, Yuta; Takabatake, Toshiro; Giester, Gerald; Rogl, Peter
Abstract: Single crystals of Ce3 Pt4 Sn6 (I) and Ce1‐x Pt6 Al13+2x (x = 0.207, (II)) are isolated by mechanical fragmentation of specimens grown from self‐fluxes (Sn or Al, resp.) by slow cooling from the melt.